Rain water detector alarm with automatic sliding window - Mat Isa, Muhammad Muizzuddin; Mohd Sofi, Mohamad Zulhaikal (2016)
The rain sensor were design to detect rain by short the circuit at the rain sensor, exactly the rain sensor was created with a coil of wire put together. Like this the water can short the coil together and the circuit will break if the rain droplet have dry. In this case, we substitute the condition push off switch to put a stop for the siren and motor to avoid any unwanted scene. The project aim is to shutoff window automatically when alert by rain to prevent the rain water enter the house. Aside of that to alert the resident when there are raining outside so they can plan their activity. The calculated parameters have been optimized using Proteus 7 software and Proteus ARES software. The software are responsible for simulation test and PCB design. The design prototype has been fabricated on a breadboard to see how it work. We having problem to adjust the resistor that hold the important role to the movement of the motor and the buzzer. The problem finally has been taken care of using Proteus simulation test